Discipulado sob a cruz: um convite ao antitriunfalismo a partir do evangelho de Marcos - Ricardo, Uelton Aguiar (2013)
This dissertation compares the theology of the Gospel of Mark with that of the neopentecostal movement. While Markan theology is interpreted as antitriumphalist, leading faith communities to recognize the Christ of the cross, the neopentecostal movement takes the opposite path. Its emphasis is on triumph, the way without the cross. I begin by considering the environment of the first Christian communities that arose after Jesus passion, death, and resurrection. I then present several reflections on the intention of the evangelist Mark when he wrote his Gospel. Finally, I deal with the particular biblico-doctrinal focus of the neopentecostal movement. The main findings of this research were: a) there is a fundamental incompatibility between the neopentecostal ideology and the theological approach of the Gospel of Mark; and b) the triumphalist perspective/ideology is not inherent only to the neopentecostal movement. Even at the time when Mark was writing his Gospel, the faith community for which he intended his work had also adopted a triumphalist view of the figure of Jesus.